2019
DOI: 10.1021/acs.est.9b04704
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Nitrogen Species Mediated Degradation of Estrogenic Disrupting Chemicals by Biochar/Monochloramine in Buffered Water and Synthetic Hydrolyzed Urine

Abstract: There is increasing concern about the severe endocrine-related health problems because of the discharge of estrogenic disrupting chemicals (EDCs) into the natural environment. In this study, we investigated the activation of monochloramine (NH 2 Cl) by biochar [pyrolyzed by cotton straw at 350 °C (Cot350), wheat straw at 350 and 700 °C (WS350 and WS700), and corn straw at 350 and 700 °C (CS350 and CS700)] for the degradation of estradiol (E2) and ethinylestradiol (EE2). Approximately 95% of parent E2 and EE2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Since a previous study has reported the impact of phosphate on the generation of ROS from the oxygen reduction reaction predominated by Fe@Fe 2 O 3 , herein four experimental conditions were built to trace the possible ROS related to the ternary ECL system. First, as shown in Figure A, in an aqueous solution of Fe@Fe 2 O 3 nanowires (Figure A curve a), typical quartet peaks (relative intensity 1:2:2:1) with a hyperfine splitting constant of α N = α H = 14.9 G were observed, which were the evident spectrum of the DMPO-OH • adduct. , However, in the PBS solution of Fe@Fe 2 O 3 nanowires (Figure A curve b), a diagram of new signals appeared (α N = 16.5 G, α H = 22.5 G), confirming the generation of H • , while the signal of OH • became unapparent because of the strong signal of H • and the superposition of the DMPO-OH • signal with the DMPO-H • signal. To check the generation of O 2 •– , the 50% methanol aqueous solution of Fe@Fe 2 O 3 nanowires was examined (Figure B curve c), and the characteristic spectrum of the DMPO-O 2 •– adduct (α N = 12.9 G, α H = 10.2 G and 1.5 G) confirmed the generation of O 2 •– .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since a previous study has reported the impact of phosphate on the generation of ROS from the oxygen reduction reaction predominated by Fe@Fe 2 O 3 , herein four experimental conditions were built to trace the possible ROS related to the ternary ECL system. First, as shown in Figure A, in an aqueous solution of Fe@Fe 2 O 3 nanowires (Figure A curve a), typical quartet peaks (relative intensity 1:2:2:1) with a hyperfine splitting constant of α N = α H = 14.9 G were observed, which were the evident spectrum of the DMPO-OH • adduct. , However, in the PBS solution of Fe@Fe 2 O 3 nanowires (Figure A curve b), a diagram of new signals appeared (α N = 16.5 G, α H = 22.5 G), confirming the generation of H • , while the signal of OH • became unapparent because of the strong signal of H • and the superposition of the DMPO-OH • signal with the DMPO-H • signal. To check the generation of O 2 •– , the 50% methanol aqueous solution of Fe@Fe 2 O 3 nanowires was examined (Figure B curve c), and the characteristic spectrum of the DMPO-O 2 •– adduct (α N = 12.9 G, α H = 10.2 G and 1.5 G) confirmed the generation of O 2 •– .…”
Section: Resultsmentioning
confidence: 93%
“…First, as shown in Figure 3A, in an aqueous solution of Fe@Fe 2 O 3 nanowires (Figure 3A curve a), typical quartet peaks (relative intensity 1:2:2:1) with a hyperfine splitting constant of α N = α H = 14.9 G were observed, which were the evident spectrum of the DMPO-OH • adduct. 24,25 However, in the PBS solution of Fe@Fe 2 O 3 nanowires (Figure 3A signal (Figure 3B curve d). Therefore, it could be inferred that three kinds of intermediate radicals were involved in the ECL process of the luminol/dissolved oxygen/Fe@Fe 2 O 3 nanowires system.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…To further quantify the contributions of various ROS/RNS to the degradation of BPA, IPV, NaN 3 , p -benzoquinone, and flavanone were used as quenching agents for • OH, 1 O 2 , O 2 – , and • NO, respectively. , DBN500 was selected as the most photoactive sample and used in this degradation experiment. It is evident that the degradation of BPA was substantially reduced after the addition of flavanone (17.5%), followed by IPV (15.63%), p -benzoquinone (8.34%), and NaN 3 (5.11%) (Figure b), which evidenced the more important role of • NO in the degradation of BPA by DBN500 relative to the tested ROS.…”
Section: Resultsmentioning
confidence: 75%
“…The solution containing BPA without DBN/DBC was irradiated under the same condition as a control. Additionally, to clarify the possible role of various free radicals in the degradation of BPA, isopropanol (IPV), 1,4-benzoquinone, NaN 3 , and flavanone as quenching agents , for • OH, O 2 – , 1 O 2 , and • NO were added to the reaction systems, respectively, before the irradiation. The concentration of BPA was detected by high-performance liquid chromatography (HPLC, Agilent 1200) equipped with an ultraviolet detector with an SB-C18 (4.6 × 150 mm 2 ) column.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Luo et al. (2019) tested ferrate (FeO 4 2− ) and Wang et al. (2019) biochar-activated monochloramine for the oxidation of selected pharmaceuticals, both with good results in the selected settings.…”
Section: Removal Of Pathogens and Organic Micropollutantsmentioning
confidence: 99%